Effect of Using Palm Kernel Shell Ash and Rice Husk Ash on Stability of Lateritic Soil for Road Pavement - SUBAIR, Sulaiman Olayinka; IBITOYE, Biliyamin Adeoye; KURANGA, Abdulrauf Toyin; OLAWALE, Opeyemi Ebenezer (ABUAD Journal of Engineering and Applied Sciences, 2024)
This study investigates the stabilization of lateritic soil sourced from a roadside along Iraa Road, near the Nigeria Navy School in Kwara State, Nigeria. The soil was sampled at a depth of 1 meter following the removal of topsoil. Initial testing revealed a California Bearing Ratio (CBR) of 27%, meeting the minimum requirements for subgrade suitability. The addition of 4% Palm Kernel Shell Ash (PKSA) and 2% Rice Husk Ash (RHA) significantly improved the CBR to 41%, reflecting enhanced load-bearing capacity. These findings align with previous research demonstrating the efficacy of PKSA and RHA in improving soil strength. However, stabilization beyond the optimal content of 4% PKSA and 2% RHA resulted in declining CBR values, underscoring the critical importance of maintaining optimal stabilizer proportions for effective performance. The study further observed an increase in the optimum moisture content (OMC) of the soil, rising from 12.60% to 16.10% upon the addition of stabilizers, consistent with the moisture requirements induced by pozzolanic materials. Similarly, the Maximum Dry Density (MDD) of the natural soil increased from 1.67 kg/m3 to 1.72 kg/m3 with the inclusion of 4% PKSA and 2% RHA, indicating enhanced compaction properties. These improvements correspond with established standards and corroborate findings from related studies. To comprehensively assess the effects of stabilization, the research also examined mixtures incorporating incremental proportions of RHA (0%, 2%, 4%, 6%, 8%, and 10%) combined with 4% PKSA, previously identified as optimal for enhancing soil properties. The goal was to improve the soil’s CBR values, particularly for application in base course construction. The results demonstrate that while PKSA and RHA are effective stabilizers, exceeding optimal levels leads to reduced performance, emphasizing the need for precise proportioning to achieve desired outcomes in lateritic soil stabilization.